Smart Sukuk: Model Blockchain Untuk Meningkatkan Transparansi Dan Mengurangi Gharar - Indra Sari; Nurhayati; Yenni Samri Juliati Nasution (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to formulate a blockchain-based Smart Sukuk model to reduce gharar and increase transparency in Islamic financial instruments through a qualitative approach based on a literature study of published literature including reports from the Financial Services Authority (OJK), the Directorate General of Public Procurement (DJPPR), the Indonesian Stock Exchange (BEI), the Indonesian Financial Services Authority (IFSB), fatwas from the National Sharia Council (DSN-MUI), and academic publications on sukuk, blockchain, and smart contracts. Descriptive-analytical and interpretive analyses indicate that blockchain has the potential to increase transparency through immutable recording and real-time audits, while smart contracts have the potential to automate payments, project monitoring, and sharia compliance, thereby minimizing asymmetric information and moral hazard. This study provides theoretical implications in the form of a conceptual framework for gharar mitigation and practical implications for regulators and Islamic capital market players in developing smart sukuk. The limitation of this study lies in its non-empirical nature, so further research is needed to test the technical implementation in practice.